Efficacy of hydrodynamic interleukin 10 gene transfer in human liver segments with interest in transplantation. Issue 1 (21st December 2016) - Sendra Gisbert, Luis; Miguel Matas, Antonio; Sabater Ortí, Luis; Herrero, María José; Sabater Olivas, Laura; Montalvá Orón, Eva María; Frasson, Matteo; Abargues López, Rafael; López‐Andújar, Rafael; García‐Granero Ximénez, Eduardo; Aliño Pellicer, Salvador Francisco
Abstract : Different diseases lead, during their advanced stages, to chronic or acute liver failure, whose unique treatment consists in organ transplantation. The success of intervention is limited by host immune response and graft rejection. The use of immunosuppressant drugs generally improve organ transplantation, but they cannot completely solve the problem. Also, their management is delicate, especially during the early stages of treatment. Thus, new tools to set an efficient modulation of immune response are required. The local expression of interleukin (IL) 10 protein in transplanted livers mediated by hydrodynamic gene transfer could improve the organ acceptance by the host because it presents the natural ability to modulate the immune response at different levels. In the organ transplantation scenario, IL10 has already demonstrated positive effects on graft tolerance. Hydrodynamic gene transfer has been proven to be safe and therapeutically efficient in animal models and could be easily moved to the clinic. In the present work, we evaluated efficacy of human IL10 gene transfer in human liver segments and the tissue natural barriers for gene entry into the cell, employing gold nanoparticles. In conclusion, the present work shows for the first time that hydrodynamic IL10 gene transfer to human liver segments ex vivo efficiently delivers a human gene into the cells. Indexes of tissue protein expression achieved could mediate local pharmacological effects with interest in controlling the immune response triggered after liver transplantation. On the other hand, the ultrastructural study suggests that the solubilized plasmid could access the hepatocyte in a passive manner mediated by the hydric flow and that an active mechanism of transportation could facilitate its entry into the nucleus. Liver Transplantation 23:50–62 2017 AASLD .